(untitled) (Eurasian Journal of Philology Science and Education, 2015)
It is well known today that all choreography art researches are interested in how and in which direction Kazakh folk dance is developed. National dances of deep meaning and of high ideological and artistic level are not so simple as «Kamazhay» and «Aygolek», aimed at performing in kindergartens and schools. The Kazakh dance with its peculiarities is a great achievement of dance art. It is important to know what many artists reached success in their development thank to hard work and deep understanding of the nature of the notion of the Kazakh dance. The article is about the art of choreography and the fact that in the history of the Kazakh dance all kinds of dances originate from the folk art sources. Currently it is becoming a very valuable heritage of a rich choreographic tradition, showing the ways of the Kazakh dance development.